Comparing efficacy and safety of low-dose versus standard-dose antiplatelet therapy in stroke patients: a meta-analysis - Zhao Ren; Chunxing Li; Xin Zhang; Lichaoyue Sun; Hui Zhu; Dongxiao Wang; Yumin Wang; Shuo Liang; Guanchun Wang (Frontiers in Pharmacology)
BackgroundStroke is the leading cause of disability globally, with antiplatelet therapy being crucial for secondary prevention but also increasing bleeding risks. This requires careful dosage adjustments to balance thrombosis and bleeding risks.ObjectiveThis study compared the efficacy and safety of low-dose versus standard-dose antiplatelet therapy in stroke patients.MethodsWe conducted a comprehensive search across multiple databases, including PubMed, Embase, the Cochrane Library, ClinicalTrials.gov, CNKI, and the Wanfang Medical Database, up to March 2024. Only randomized controlled trials assessing low-dose antiplatelet therapy in stroke patients were considered. The Cochrane Risk of Bias Tool (RoB 2) was used for quality. Performed meta-analysis using Stata 15.0, with relative risk (RR) and 95% confidence interval (CI) as effect estimates.ResultsTen studies involving 7,703 Asia participants, mainly from China and Japan, were analyzed. The meta-analysis revealed that low-dose reduces the risk of bleeding (RR 0.51; 95% CI 0.27, 0.98) compared to standard dose, with similar risks for stroke (RR 1.04; 95% CI 0.69, 1.55), myocardial infarction (MI) (RR 1.91; 95% CI 0.88, 4.12), all-cause death (ACD) (RR 1.17; 95% CI 0.38, 3.62), and major bleeding (RR 0.74; 95% CI 0.16, 3.30). Subgroup analysis revealed that compared to standard-dose clopidogrel, low-dose clopidogrel increased the risk of MI. Notably, this increased risk was observed specifically within the Chinese population but not in the Japanese population. Low-dose clopidogrel and low-dose prasugrel reduce the risk of bleeding compared to standard-dose clopidogrel, but there is no statistically significant difference. Low-dose aspirin significantly reduces the risk of bleeding compared to standard-dose aspirin.ConclusionIn patients with stroke in Asia, low-dose antiplatelet therapy significantly reduces the risk of bleeding compared to standard doses, with consistent risks of stroke, MI, ACD, major bleeding, and discontinuation due to bleeding.